2019
DOI: 10.1177/0391560319845255
|View full text |Cite
|
Sign up to set email alerts
|

Transobturator tape and mini-sling methods in stress urinary incontinence: Results of a randomized clinical trial

Abstract: Background: Stress urinary incontinence is one of the most common types of incontinence in premenopausal women, accounting for almost 50% of such cases. Mid-urethral slings are currently the most widely used surgical method for stress urinary incontinence. This study aimed at comparing the efficacy, complications, urodynamic changes and the sexual function status between mini-sling surgery and transobturator tape to help us select the best method in such patients. Method: In this randomized controlled trial, 8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 10 publications
3
2
0
Order By: Relevance
“…are similar to what was mentioned by other study [18] as mean operative time was 25 + 9.48 min and also consistent with another one [19] which reported a mean surgical time of 6.9 ± 1.83 min in the mini-sling which was significantly less than that reported in the TOT group 11.5 ± 5.01 min. Operative time was shorter in group I as there was no need for skin or groin incision and no need for trans obturator passage.…”
Section: Baseline Characteristics Of the Studied Groupssupporting
confidence: 92%
See 2 more Smart Citations
“…are similar to what was mentioned by other study [18] as mean operative time was 25 + 9.48 min and also consistent with another one [19] which reported a mean surgical time of 6.9 ± 1.83 min in the mini-sling which was significantly less than that reported in the TOT group 11.5 ± 5.01 min. Operative time was shorter in group I as there was no need for skin or groin incision and no need for trans obturator passage.…”
Section: Baseline Characteristics Of the Studied Groupssupporting
confidence: 92%
“…The intra-operative blood loss was insignificantly different between both groups which agreed with what was reported by other studies [20,21] but pervious study [19] stated that the mini-sling group demonstrated significantly less blood loss than the other group. Another study [8] reported 47.7 ml blood loss during using surgeon tailored needleless mesh and this was similar to our results.…”
Section: Baseline Characteristics Of the Studied Groupssupporting
confidence: 90%
See 1 more Smart Citation
“…IQ: Interquartiles. Table(5) showed that: among the studied cases; leak was reported in less than half of cases (44.3%).Total=79. IQ: Interquartiles.…”
mentioning
confidence: 89%
“…4 When conservative treatment fails, the surgical treatment is resorted in the form of mid urethral slings. 5 The most common performed procedures now for treating SUI are the mid urethral slings are currently TOT and tension free vaginal tape (TVT) on top of these procedures. 6 The common point of mid urethral sling operations is the use of mesh material passed under the urethra.…”
Section: Introductionmentioning
confidence: 99%